Acid degradation of thermoset materials - Lim, Jacob Song Kiat (Nanyang Technological University, 2020)
Thermoset polymers are a class of materials known for its insolubility in solvent due to its crosslinked network, which consequently impart upon it a high degree of chemical resistance. However, the degradation of thermoset materials upon exposure to strongly acidic conditions are not well understood by the scientific community due to a surprising lack of established research work in this topic. Often, it is presumed that acid degradation of polymer is chemical in nature, and thus the physical diffusion aspect tends to be overlooked. This research work intends to study and understand both the chemical and physical degradation behaviour of thermoset materials under strong acids, thus facilitating the identification of acid resistant or susceptible moieties, which may then either enable the design of an acid resistant thermoset material or allow for the development of a process to recycle thermosets.